Афоризми К. Крауса: структурно-семантичні особливості - Свєрчкова, Марія Володимирівна; Svierchkova, M. V. (Харків : Харківський національний університет імені В. Н. Каразіна, 2024)
The work is devoted to the study of aphorisms of the Austrian writer and journalist Karl Kraus and their structural and semantic features. The scientific novelty lies in the in-depth study of the structure of aphorisms and in the analysis of a separate group of K. Kraus's aphorisms, in particular their structural and semantic features and their influence on the further development of aphorism and language in general. The following research methods were used to accomplish the tasks: study and analysis of scientific and specialized literature; classification and generalization of the collected material; method of linguistic observation and description; methods of contextual analysis. The object of the study is the aphoristic sayings of the Austrian writer K. Kraus. The subject of the study is the structural and semantic features of Germanlanguage aphoristic expressions.

Роботу присвячено вивченню афоризмів австрійського письменника і журналіста Карла Крауса та їх структурно-семантичних особливостей. Наукова новизна полягає в поглибленому вивченні структури афоризмів та аналізі окремої групи афоризмів К. Крауса, зокрема їх структурно-семантичних особливостей та впливу на подальший розвиток афористики та мови в цілому. Для виконання поставлених завдань використовувалися наступні методи дослідження: вивчення та аналіз наукової та спеціальної літератури; класифікація та узагальнення зібраного матеріалу; метод лінгвістичного спостереження та опису; методи контекстного аналізу. Об’єктом дослідження є афористичні вислови австрійського письменника К. Крауса. Предметом дослідження є структурно-семантичні особливості німецькомовних афористичних висловів.
Aphorisms of Karl Kraus: structural and semantic features
Керівник : Оніщенко Наталія Анатоліївна, кандидат філологічних наук, доцент, доцент кафедри романо-германської філології
Keywords: HUMANITIES and RELIGION; афоризм; aphorism; малі літературні форми; семантичні особливості; структурні особливості; semantic features; structural features; small literary forms